Epidemiology of breast cancer in a tertiary oncology hospital in the countryside of Minas Gerais - de Oliveira, Luiz Carlos Navarro; Castro, Sebastião Maurício de Oliveira; de Freitas, Carla Simone Moreira; Silva, Rita de Cássia de Jesus Duarte; Vieira, Flávio Ferraz; Tostes, Rodrigo Bastos; Melo, Bruno Licy Gomes de; Vieira, René Aloisio da Costa (Mastology, 2024)
Objective: In Brazil, the characteristics of breast cancer patients who arrive at cancer treatment services are influenced by conditions related to the tumor, to the diagnostic system and navigation in the phase prior to care, with regional differences being little known as well as their seasonal variation. Methods: This is a retrospective study of epidemiological data of patients with breast cancer treated at the Hospital do Câncer de Muriaé (HCM), an exclusively oncology hospital (CACON II), with primarily public care, a reference for cancer treatment in the east of Zona da Mata region, Minas Gerais. Clinical and care-related characteristics were evaluated from 2010 to 2021. Results: During this period, 4,573 new patients were treated. The care was primarily public (80.5%) and most patients were undiagnosed (45.7%) or untreated (71.8%) at the first visit. The patients were between 40 and 69 years old (70.2%) and a significant portion were between 70 and 74 years old (7.4%). The rate of early stage (clinical stage – CS 0 + I) represented only 33.9 and 25.8% of all patients and those treated exclusively in the hospital, respectively. There was no change in clinical stage and age group over the years. Conclusion: When evaluating epidemiological data, the characteristics of the service and the pre-institutional diagnostic care network should be analyzed, facts that influence the results. Throughout the period, there was no great variation in relation to age group and staging. In this region, the early stage of breast cancer has unsatisfactory rates, and the 70 to 74 age group should be considered in mammographic screening. Epidemiological studies are essential to improve health strategies.